EQUILIBRIUM DETERMINATION, TWO-SIDED MARKETS AND PLATFORMS COMPETITION: THE NIGERIAN MOBILE COMMUNICATION MARKET - Amos, Atsiya; Akawu, Francis Audu (Advances in Social Sciences Research Journal, 2018)
This study develops a theoretical model for analyzing two-sided markets that allow for global multi-homing among agents in a mobile communication market. The model explains the determination of equilibrium outcome, price structure and consumer surplus given competitive platforms and non-exclusivity of services in the Nigerian Mobile communication market. Multiple equilibria, as well as maximum platform profit from monopoly rent with associated deadweight losses on the side of the buyers, are feasible given the market structure. The existing pricing structure is seemingly suboptimal of a social welfare. The unique characteristic of the market having mixed features of monopoly and perfect competition appears to be critical in reaching the theoretical model outcome. Consumer welfare is likely to be promoted with strict enforcement of anti-trust policy needed to regulate any form of collusion.